2021
DOI: 10.3390/molecules26185572
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction or Purification Process of Multiple Components from Natural Products: Entropy Weight Method Combined with Plackett–Burman Design and Central Composite Design

Abstract: In this paper, the optimization of the extraction/purification process of multiple components was performed by the entropy weight method (EWM) combined with Plackett–Burman design (PBD) and central composite design (CCD). We took the macroporous resin purification of Astragalus saponins as an example to discuss the practicability of this method. Firstly, the weight of each component was given by EWM and the sum of the product between the componential content and its weight was defined as the comprehensive scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, few studies were reported about the optimization of extraction conditions of carotenoids from D. parva , which is rich in oil and carotenoids. Here, the CCD method, a widely used method, was used to optimize the extraction conditions [ 59 , 60 ]. Firstly, the extraction efficiencies of 7 kinds of solvents (petroleum ether, ethyl acetate, 95% ethanol, n-hexane, ethanol, DMSO and acetone) were compared.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies were reported about the optimization of extraction conditions of carotenoids from D. parva , which is rich in oil and carotenoids. Here, the CCD method, a widely used method, was used to optimize the extraction conditions [ 59 , 60 ]. Firstly, the extraction efficiencies of 7 kinds of solvents (petroleum ether, ethyl acetate, 95% ethanol, n-hexane, ethanol, DMSO and acetone) were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The information of an evaluation index is of great significance, the entropy value is low, and should be assigned a high weight coefficient to indicate its importance [18]. The EWM method determines the weight of each indicator in the following way [19]:…”
Section: Entropy Weight Methodsmentioning
confidence: 99%
“…The information of an evaluation index is of great significance, the entropy value is low, and should be assigned a high weight coefficient to indicate its importance [18]. The EWM method determines the weight of each indicator in the following way [19]: Xbadbreak=xijm×n(i=1,2,m;j=1,2,n).$$\begin{equation}X = {\left\{ {{x}_{ij}} \right\}}_{m \times n}(i = 1,2 \cdots ,m;j = 1,2 \cdots ,n).\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…There were m objects with n indexes to be evaluated in the index system then the matrix was evaluated as follows [32] : …”
Section: Methodsmentioning
confidence: 99%